Analysis of Factors against Audit Delay in Service Companies Listed on the IDX in 2017-2019 - Jessica, Jessica; Valentina, Valentina; Hutahaean, Thomas Firdaus (Budapest International Research and Critics University, 2021)
The research was conducted to determine the effect, analyze and gain an understanding of whether Auditor's Reputation, Company Size, Auditor's Opinion, Length of Assignment, and Auditor Changes partially or simultaneously affect Audit Delay in service companies listed on the IDX in 2017-2019. This study uses descriptive research with a qualitative approach to determine the factors that cause an event. Researchers used multiple linear regression analysis as a research method. In this study, there were a population of 413 companies and a sample of 246 service companies in 2017-2019. Auditor's Reputation, Company Size, and Auditor's Opinion have no influence and significant impact on Audit Delay in service companies listed on the IDX in 2017-2019. Meanwhile, the Length of Assignment, and Auditor Changes have no influence and insignificant effect on Audit Delay in service companies listed on the IDX in 2017-2019. From the research that has been done, it can be concluded that the coefficient of determination R-Squared (R2) is 0.237 or means 23.7% and the remaining 76.3% is not included in the variables.